If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 + 2y + 8 = 142 Reorder the terms: 6 + 8 + 4x + 2y = 142 Combine like terms: 6 + 8 = 14 14 + 4x + 2y = 142 Solving 14 + 4x + 2y = 142 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + 4x + -14 + 2y = 142 + -14 Reorder the terms: 14 + -14 + 4x + 2y = 142 + -14 Combine like terms: 14 + -14 = 0 0 + 4x + 2y = 142 + -14 4x + 2y = 142 + -14 Combine like terms: 142 + -14 = 128 4x + 2y = 128 Add '-2y' to each side of the equation. 4x + 2y + -2y = 128 + -2y Combine like terms: 2y + -2y = 0 4x + 0 = 128 + -2y 4x = 128 + -2y Divide each side by '4'. x = 32 + -0.5y Simplifying x = 32 + -0.5y
| -7n-2=16 | | y^2-6y-5x=-14 | | -0.21=log(x) | | 20+130+p=180 | | 4t+17=7+5f | | 25x^3-10x= | | x^4+4x^2+1=0 | | X=y^2-6 | | -8(2-x)=416 | | 3x+2=96 | | (x-2)squared=50 | | (x^3+x^2+x+1)(13x-9)= | | 6k-16=2k+4 | | (x^4-x^2-2x+6)=0 | | (8-6i)-4=x-(1+yi) | | -3(2p+14)-28=2(p+15)+12 | | 6x-3=4(x+22) | | -11+4n=5-(11+17) | | (x^3-x^2-2)=0 | | .7(-3X-2)=3.5+1 | | -11+4n=5-(11+12) | | 6x+-10=110 | | 5x(x^3-x^2-2)=0 | | 20+2.50(19)=x | | 20+2.50(20)=x | | 20+2.50(18)=x | | 20+30+p=180 | | -9.1=k-6.3 | | 20+2.50(17)=x | | 3.2+d=5 | | 5x^2+41x-54=0 | | 20+2.50(16)=x |